Pseudo phase plane, delay and fractional dynamics - Lima, Miguel Francisco Martins (2008)
This paper analyses the relationship between the signal delay and the fractional dynamics. It is shown that some experimental signals spectra are approximated by trendlines. Based on the slope of these trendlines the fractional or integer order behavior is determined. For the pseudo phase plane reconstruction of each signal, the time delays are calculated through the fractal dimension, as an alternative to the mutual information that is often used. The slopes of the trendlines spectra reveal a relationship with the fractal dimension of the pseudo phase plane and the corresponding time lag.